A multi-modal wideband magnetoelectric energy harvesting structure and method of fabrication
Patent Information
- Application Number
- CN202611083634.7
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2026-07-21
- Publication Date
- 2026-10-30
AI Technical Summary
针对现有技术中磁电(ME)能量收集器件存在的频带窄、小尺寸下难以拓宽频率范围、结构复杂、层间结合稳定性差等缺陷,本发明提供一种多模态宽频磁电能量收集结构,通过浓度梯度压电层的无粘合层一体化设计,实现多振动峰响应,在1cm×1cm的小尺寸前提下,大幅拓宽磁场能量收集的频率范围,同时有效提升磁电转换效率与结构稳定性,解决现有技术的应用痛点
(1)多模态宽频响应,适配弱磁场宽频收集:通过P(VDF-TrFE)/BTO-OH复合层的浓度梯度设计,结合各层厚度的差异化调控,使器件的振动响应从传统的单一共振峰转变为多稳定振动峰,能量收集频率范围拓宽至1~10kHz,相较于传统单一浓度纯ME器件拓宽90%以上,能够高效捕获环境中随机变化的弱磁场能量,适配不同场景下的能量收集需求。
Smart Images

Figure CN123019498A_ABST
Abstract
Description
Technical Field
[0001] This invention belongs to the field of magnetoelectric energy harvesting technology, and particularly relates to a multi-mode broadband magnetoelectric energy harvesting structure and its preparation method. Background Technology
[0002] Magnetoelectric energy harvesting technology achieves energy conversion and harvesting through the magnetostrictive-piezoelectric coupling effect, and has broad application prospects in self-powered electronic systems. Most existing layered magnetoelectric energy harvesting structures are composed of a single concentration of piezoelectric layer and magnetostrictive layer. Due to the inherent characteristics of the magnetoelectric composite material, its vibration response has only a single resonance peak, resulting in a relatively narrow frequency range for energy harvesting, making it difficult to efficiently capture the energy of randomly changing weak magnetic fields in the environment.
[0003] To broaden the operating frequency band of energy harvesting, existing technologies often employ multi-cantilever beam arrays or large-size structural designs. However, multi-cantilever beam arrays are complex and have low integration, making them difficult to adapt to the installation requirements of microelectronic devices. Large-size structures, on the other hand, cannot meet the miniaturization and lightweight requirements of microelectronic devices, further limiting the application of magnetoelectric energy harvesting technology in the field of microelectronics.
[0004] Meanwhile, the piezoelectric properties of the piezoelectric composite layer are closely related to the concentration of the ceramic filler; different concentrations of ceramic filler correspond to different piezoelectric constants. d 33 And resonant frequency. Existing technologies do not fully utilize the concentration gradient of ceramic fillers to modulate the vibration characteristics of piezoelectric layers, and cannot achieve multimodal vibration response through a single structure, making it difficult to overcome the technical bottleneck of broadband magnetic field energy harvesting in small-size scenarios. In addition, traditional magnetoelectric energy harvesting structures often incorporate mass blocks or adhesive layers, which not only result in high energy loss but also reduce the stability of interlayer bonding, further limiting the improvement of magnetoelectric conversion efficiency. For example, the traditional scheme of bonding a single-concentration piezoelectric layer (such as PVDF / Metglas devices, size 0.5cm×3cm×84mm) with a magnetostrictive layer under a weak magnetic field test condition of 0.05Oe has an effective energy harvesting bandwidth of only about 1.3kHz and an output voltage of only about 0.42V. Moreover, the strain transfer loss due to the introduction of the adhesive layer is about 30%, which is difficult to meet the actual requirements of micro self-powered devices for broadband and high output. Summary of the Invention
[0005] To overcome the problems existing in related technologies, the present invention discloses a multimodal broadband magnetoelectric energy harvesting structure and its fabrication method, which is particularly suitable for magnetoelectric (ME) energy harvesting devices. It can be used to harvest energy from weak environmental magnetic fields and provide self-powered support for low-power electronic devices such as wireless sensors and IoT nodes. Addressing the shortcomings of existing magnetoelectric (ME) energy harvesting devices, such as narrow bandwidth, difficulty in widening the frequency range under small size, complex structure, and poor interlayer bonding stability, the present invention provides a multimodal broadband magnetoelectric energy harvesting structure. Through an integrated design of a concentration gradient piezoelectric layer without adhesive layers, it achieves a multi-vibration peak response, significantly widening the frequency range of magnetic field energy harvesting within a small size of 1cm × 1cm, while effectively improving magnetoelectric conversion efficiency and structural stability, thus solving the application pain points of existing technologies.
[0006] The technical solution is as follows: a multimodal broadband magnetoelectric energy harvesting structure, which includes a concentration gradient piezoelectric layer assembly, a magnetostrictive layer, and a silver electrode layer; the concentration gradient piezoelectric layer assembly is integrally formed by spin coating of an upper piezoelectric composite layer, a middle piezoelectric composite layer, and a lower piezoelectric composite layer, with no adhesive layer between the layers; the magnetostrictive layer is tightly bonded to the lower piezoelectric composite layer, and the silver electrode layer covers the upper piezoelectric composite layer, forming a flat, compact magnetoelectric energy harvesting structure.
[0007] Furthermore, the upper, middle, and lower piezoelectric composite layers all adopt the P(VDF-TrFE) / BTO-OH composite system and are prepared layer by layer by spin coating; the overall planar dimensions of the concentration gradient piezoelectric layer assembly are 1cm × 1cm.
[0008] Furthermore, the volume concentration of BTO-OH inside the upper, middle, and lower piezoelectric composite layers exhibits a continuously increasing gradient distribution along the thickness direction, with the BTO-OH volume concentration ranging from 3.75% to 16%, and the concentration difference between adjacent layers controlled within 3% to 7%.
[0009] Furthermore, the optimal volume concentration of BTO-OH in the lower piezoelectric composite layer is 14% to 15.5%.
[0010] Furthermore, the magnetostrictive layer is made of amorphous alloy material with a planar dimension of 1cm×1cm; the silver electrode layer is made of highly conductive silver electrode and is prepared on the upper surface of the upper piezoelectric composite layer by a coating process.
[0011] Another object of the present invention is to provide a method for fabricating a multimode broadband magnetoelectric energy harvesting structure. This method is used to fabricate the multimode broadband magnetoelectric energy harvesting structure, and includes: S1. Preparation of P(VDF-TrFE) / BTO-OH composite slurry; S2. Complete the hot-pressing composite of the magnetostrictive layer; S3. A concentration gradient piezoelectric layer assembly was prepared using a spin coating method. S4. Prepare the silver electrode layer and complete the overall encapsulation.
[0012] In step S1, the preparation of P(VDF-TrFE) / BTO-OH composite slurry includes: P(VDF-TrFE) / BTO-OH composite slurries with volume concentrations of 3.75%, 7.5%, and 15% were prepared respectively. Using N,N-dimethylformamide (DMF) as a solvent, P(VDF-TrFE) powder and BTO-OH particles were mixed in proportion. The particles were ultrasonically dispersed for 2 hours to ensure uniform dispersion, and then ultrasonically degassed for 30 minutes at 200W power to remove air bubbles, resulting in a uniform and stable composite slurry.
[0013] In step S2, the hot-pressing composite of the magnetostrictive layer includes: A temporary support structure was used to fix the Metglas amorphous alloy sheet, and hot-pressing composite was carried out under the process conditions of 140℃, 120 min holding time, and 0.8–1.2 MPa pressure to obtain a stable magnetoelectric composite substrate.
[0014] In step S3, the concentration gradient piezoelectric layer assembly is prepared by spin coating, including: The magnetoelectric composite substrate was fixed on the stage of a spin coater. A 15% concentration composite slurry was first applied to the surface of a Metglas alloy sheet. The spin coating speed was 1200 rpm and the spin coating time was 30 s. Then, it was heat-cured at 120°C for 30 min to form the lower piezoelectric composite layer. After cooling to room temperature, the same process was used to spin coat 7.5% and 3.75% concentration composite slurries. Each layer was heat-cured at 120°C for 30 min. The layers were stacked one by one to form a gradient piezoelectric structure without an adhesive layer. The middle piezoelectric composite layer and the upper piezoelectric composite layer were formed in sequence.
[0015] Furthermore, the concentration gradient piezoelectric layer assembly adopts a five-level gradient concentration layer design, with the five gradient volume concentrations being 3.75%, 5.5%, 7.5%, 11%, and 15% respectively, forming a continuously gradually changing concentration gradient piezoelectric structure.
[0016] Combining all the above technical solutions, the beneficial effects of this invention are as follows: (1) Multimodal broadband response, adaptable to weak magnetic field broadband harvesting: By designing the concentration gradient of the P(VDF-TrFE) / BTO-OH composite layer and combining the differential control of the thickness of each layer, the vibration response of the device is transformed from the traditional single resonance peak to multiple stable vibration peaks, and the energy harvesting frequency range is broadened to 1~10kHz, which is more than 90% wider than the traditional single concentration pure ME device. It can efficiently capture the energy of randomly changing weak magnetic fields in the environment and adapt to the energy harvesting needs in different scenarios.
[0017] (2) Small size and high integration, suitable for microelectronic devices: In the prior art, in order to broaden the frequency band, multiple cantilever beam arrays or large-size mass block designs are often used, which makes it difficult to control the planar size within 1cm² or the thickness exceeding 500μm, which cannot meet the surface mounting requirements of microelectronic devices; while the adhesive layer process not only increases the thickness, but also introduces strain transfer loss (the traditional bonding efficiency is only 70%-80%). This invention, through an integrated design without adhesive layer, precisely controls the overall planar size of the device to 1cm×1cm, with a total thickness ≤137μm (total thickness of concentration gradient piezoelectric layer 90-100μm + magnetostrictive layer 32μm + electrode layer 5μm). It adopts a flat mass block-free design, which is compact and highly integrated. It does not require a complex mechanical excitation module and can be directly attached to the surface of small devices such as micro wireless sensors and IoT nodes, effectively solving the adaptation problem of the excessively large size of traditional broadband collection structures. In existing technologies, multi-cantilever beam arrays trade area for bandwidth, resulting in planar dimensions ≥ several square centimeters, which cannot be ≤ 1cm²; existing mass block designs trade thickness for frequency, resulting in thicknesses > 500μm, which cannot be planarly bonded; existing technologies increase the thickness by 10-30μm, but the strain transfer efficiency is only 70%-80%, and the accumulation of adhesive layers further deteriorates the integration. This invention achieves a 1cm² wideband response by spin coating, eliminating the need for multiple vibration spaces; the adhesive-free design eliminates the need for adhesive layer thickness, with a total thickness ≤137μm; strain transfer efficiency >95%, surpassing the efficiency of small-size designs; this invention achieves a wideband response in a 1cm² plane for the first time by using differentiated technical paths such as concentration gradient instead of mechanical array, adhesive-free instead of adhesive layer composite, and pure ME conversion instead of mass block excitation, breaking through the technical bottleneck that miniaturization and wideband response cannot be achieved simultaneously.
[0018] (3) Pure ME conversion is highly efficient and stable, with excellent energy output performance: The bottom composite layer of the concentration gradient piezoelectric layer component 2 adopts the optimal concentration design of BTO-OH (the optimal concentration range is 13%-16%, preferably 14%-15.5%, while satisfying d 33 ≥40pC / N, dielectric loss tanδ≤0.05, film density ≥95%, piezoelectric constant d 33With a strength of ≥40pC / N, the combination of a magnetostrictive layer and a piezoelectric layer significantly improves the magnetoelectric coupling efficiency. At the same time, the pure ME energy conversion mechanism eliminates wear on vibrating components, extending the device's lifespan to over 5000 hours and significantly enhancing its stability, enabling long-term stable operation.
[0019] (4) Integrated fabrication without adhesive layer, simple process and easy to scale up: The concentration gradient piezoelectric layer component is formed by layering and heating through spin coating, without the need for additional adhesive layer. This not only simplifies the preparation process and reduces the process cost, but also improves the interlayer bonding strength by 30% compared with the traditional adhesive structure. The thickness parameters of each layer can be precisely controlled by spin coating speed. The consistency of the device is good during mass production, which is suitable for large-scale industrial production.
[0020] As supplementary evidence of the inventive step for the claims of this invention, it is also reflected in the following important aspects: (1) The expected benefits and commercial value of the technical solution of this invention after transformation are as follows: (A) Cost Reduction and Efficiency Improvement Benefits of Downstream Self-Powered Hardware: This device can be directly mounted in scenarios such as passive IoT sensors, temperature / vibration measurement nodes in industrial equipment, wireless switches in smart homes, wearable medical monitoring devices, and low-voltage sensing modules in rail transit, without the need for external batteries or charging lines, significantly reducing the costs of battery procurement, regular replacement, and wiring maintenance. Traditional sensor nodes powered by button batteries have an average battery replacement cycle of 6–12 months, with an average annual maintenance cost of tens of yuan per device. After adopting this magnetoelectric energy harvesting device, the device's self-powered lifespan can reach over 5000 hours, requiring no power supply maintenance throughout the entire lifespan. For a single batch of millions of IoT terminals, this can save tens of millions of yuan in maintenance expenses.
[0021] (B) Economic benefits of large-scale device manufacturing: The overall preparation only adopts simple processes such as spin coating, hot pressing and coating, without precision micro-machining, multi-layer bonding and mechanical cantilever / mass block assembly process. The raw materials are only P (VDF-TrFE), modified barium titanate, amorphous alloy and conductive silver paste. The raw materials are readily available and the equipment investment threshold is low. The absence of adhesive layer eliminates the need for adhesive and alignment bonding process, reducing the manufacturing cost of a single device. It is suitable for mass production on a large production line and has a strong potential for industrialization.
[0022] (C) Added value of derivative technologies: This concentration gradient piezoelectric spin coating integrated process can be extended to the development of related devices such as piezoelectric sensors, flexible vibration energy harvesting, and ultrasonic transducers. Enterprises can rely on this core process to form a series of patented product matrices and provide material formulations, device customization, and process solution technology licensing to external parties, thus opening up a profit channel for technical services.
[0023] (2) The technical solution of this invention fills a technical gap in the industry both domestically and internationally: (A) The technological gap between miniaturization and broadband compatibility: There are only two mainstream routes for broadening the bandwidth of existing magnetoelectric energy harvesting devices at home and abroad: multi-cantilever beam arrays and adding mass block structures. The former generally has a planar size larger than several square centimeters, and the latter has a device thickness of over 500μm. Neither of them can achieve a thin and broadband response of a flat plate under an extremely small 1cm² plane. The industry has long lacked a broadband magnetoelectric harvesting scheme with an ultra-thin 1cm×1cm flat plate, no mechanical array, and no mass block. This invention is the first to use a concentration gradient piezoelectric layer to replace the mechanical array to achieve multimodal resonance, filling the gap in this subdivided structural design.
[0024] (B) Gap in high-efficiency magnetoelectric conversion devices with ultra-low size in weak magnetic fields: Existing pure ME devices of the same size (1cm²) have an effective bandwidth of only about 1kHz and an output voltage of less than 0.5V, which cannot cover random magnetic fields in the environment of 1–10kHz; This three-layer gradient structure has a bandwidth of 6.3kHz, and a five-layer gradient can reach 7.7kHz, which is more than 384% higher than the bandwidth of traditional devices and 185% higher in output voltage, filling the gap in micro-weak magnetic field wideband high-output magnetoelectric energy harvesting devices.
[0025] (3) Whether the technical solution of the present invention solves the technical problem that people have long wanted to solve but have never been able to solve successfully: (A) Challenge 1: The trade-off between miniaturization and wideband energy harvesting: To broaden the operating bandwidth, the device area must be increased, cantilever arrays added, or mass blocks installed. Conversely, shrinking the size results in a single resonance peak and a drastically narrowed effective bandwidth; both are mutually exclusive. For many years, the industry has been forced to choose one over the other, unable to achieve miniaturization and wideband simultaneously. Solution: Abandoning the mechanical array and mass block approach, this solution utilizes the piezoelectric filler concentration gradient to control the resonant frequency of each layer. A single 1cm² flat plate structure generates multiple independent resonance peaks, significantly broadening the bandwidth within an extremely small size and completely resolving this dilemma.
[0026] (B) Challenge 2: Traditional single-concentration piezoelectric layers have limited piezoelectric performance, outputting only about 0.4V under a weak magnetic field of 0.05Oe for the same size, insufficient to support the operation of wireless sensor chips; adjusting the filler concentration easily leads to side effects such as a decrease in piezoelectric constant, an increase in dielectric loss, and film cracking, making it difficult to balance piezoelectric performance and film quality. Solution: Match the bottom layer with an optimal BTO-OH concentration of 14%-15.5%, balancing high performance and low dielectric loss. With low dielectric loss, high film density, and multi-layer gradient synergistic coupling magnetostrictive layer, the output voltage is increased to over 1.2V, which can directly drive passive sensing chips and solve the problem of insufficient energy output under weak magnetic fields.
[0027] (4) Does the technical solution of the present invention overcome technical bias? (A) The industry's inherent understanding that broadening the magnetoelectric collection bandwidth can only rely on mechanical structure design (cantilever array, mass block) is that piezoelectric materials have fixed resonant characteristics and can only generate multiple resonance peaks by changing the mechanical structure and adding multiple sets of vibration units. Simply adjusting the piezoelectric material filler concentration cannot achieve a wideband multimodal response. This invention overcomes this prejudice: it breaks away from the mechanical structure improvement approach and innovatively utilizes the piezoelectric ceramic filler concentration gradient to change the elastic modulus, piezoelectric constant, and inherent resonant frequency of each piezoelectric film layer. Multiple vibration peaks can be formed in a single flat plate structure solely by relying on the material composition gradient, without any auxiliary mechanical vibration structure. This proves that material gradient control is a new and feasible path for wideband design.
[0028] (B) Piezoelectric filler concentration gradients significantly increase film dielectric loss and degrade magnetoelectric conversion performance: Existing research generally believes that differences in the concentration of multilayer ceramic fillers cause uneven stress within the film, increasing dielectric loss and weakening the overall magnetoelectric coupling efficiency. Gradient design is therefore counterproductive, and a single, uniform filler concentration piezoelectric layer is preferred. This invention overcomes this bias: by limiting a reasonable concentration range of 3.75%-16%, controlling a moderate interlayer concentration difference of 3%-7%, and matching the optimal concentration of the bottom layer, the overall dielectric loss of the gradient film is tanδ≤0.05. The piezoelectric performance is layered and complementary, and the overall conversion efficiency after multi-peak coupling is much higher than that of a single-concentration film. This proves that controllable gradient design does not degrade performance but rather significantly improves the overall energy harvesting capability.
[0029] (C) The 1cm² micro-planar structure cannot achieve wideband energy harvesting above 1kHz: Industry testing generally concludes that when the planar size is reduced to 1cm², the structural stiffness of the device increases and the resonance range narrows, making it difficult to break through 2kHz in effective bandwidth. Micro-devices are only suitable for narrowband fixed-point magnetic field acquisition and cannot adapt to random wideband magnetic fields in the environment. The three-layer gradient structure has an effective bandwidth of 6.3kHz, and the five-layer gradient can reach 7.7kHz, achieving an ultra-wideband response in an extremely small 1cm² plane. This breaks the inherent technical understanding that the bandwidth of micro-planar devices is limited and subverts the inherent design concept of narrowband application of small-size magnetoelectric devices. Attached Figure Description
[0030] The accompanying drawings, which are incorporated in and form part of this specification, illustrate embodiments consistent with the disclosure of this invention and, together with the description, serve to explain the principles of this disclosure; Figure 1 This is a schematic diagram of the multimodal broadband magnetoelectric energy harvesting structure provided in an embodiment of the present invention; Figure 2 This is a schematic cross-sectional view of the concentration gradient piezoelectric layer assembly provided in an embodiment of the present invention; Figure 3 This is a flowchart illustrating the fabrication method of the multimodal broadband magnetoelectric energy harvesting structure provided in this embodiment of the invention. Figure 4Vibration response diagram of a conventional structure of the same thickness; Figure 5 This is a diagram showing the vibration response of the structure of the present invention. In the figure: 1. Silver electrode layer; 2. Concentration gradient piezoelectric layer assembly; 3. Magnetostrictive layer; 4. Upper piezoelectric composite layer; 5. Middle piezoelectric composite layer; 6. Lower piezoelectric composite layer; Detailed Implementation To make the above-mentioned objects, features, and advantages of the present invention more apparent and understandable, specific embodiments of the present invention will be described in detail below with reference to the accompanying drawings. Many specific details are set forth in the following description to provide a thorough understanding of the present invention. However, the present invention can be practiced in many other ways different from those described herein, and those skilled in the art can make similar modifications without departing from the spirit of the present invention. Therefore, the present invention is not limited to the specific embodiments disclosed below.
[0031] The innovation of this invention lies in addressing the challenges of miniaturization and broadband compatibility, high bonding loss, and low output in existing magnetoelectric harvesting devices. This invention proposes a concentration gradient P(VDF-TrFE) / BTO-OH adhesive-free integrated magnetoelectric energy harvesting structure and its fabrication method. The structure is formed by spin-coating and layer-by-layer curing. The piezoelectric layer has a BTO-OH concentration gradient distribution of 3.75%-16%, while the bottom layer uses an optimal concentration of 14%-15.5% combined with a Metaglas amorphous alloy to achieve pure magnetoelectric coupling. Multi-mode broadband response is achieved through multi-layer differential resonance. The device size is only 1cm × 1cm, with a total thickness ≤137μm. Tests show that the three-layer gradient device has an effective bandwidth of 6.3kHz, a 384.6% improvement over traditional devices, a peak output voltage of 1.20V, a strain transfer efficiency >95%, and a lifespan exceeding 5000 hours. This fabrication process is simple and easy to mass-produce, providing a novel solution for self-powering micro-passive sensing devices with weak magnetic fields.
[0032] Example 1.
[0033] The present invention is based on the composite design of concentration gradient piezoelectric layer components and magnetostrictive layers, which utilizes the BTO-OH concentration gradient to regulate the piezoelectric properties and vibration characteristics of each layer, thereby achieving multimodal broadband energy harvesting.
[0034] Figures 1-2 As shown, the multimodal broadband magnetoelectric energy harvesting structure provided in this embodiment of the invention includes a concentration gradient piezoelectric layer assembly 2; the concentration gradient piezoelectric layer assembly 2 is integrally formed by spin coating of an upper piezoelectric composite layer 4, a middle piezoelectric composite layer 5, and a lower piezoelectric composite layer 6, with no adhesive layer between the layers; a magnetostrictive layer 3 is tightly bonded to the lower piezoelectric composite layer 6, and a silver electrode layer 1 covers the upper piezoelectric composite layer 4, forming a flat and compact structure that is suitable for installation and use in microelectronic devices.
[0035] For example, a concentration gradient piezoelectric layer assembly 2 is designed, consisting of at least three layers of piezoelectric composite layers without adhesive layers. Each layer adopts a P(VDF-TrFE) / BTO-OH composite system and is prepared layer by layer by spin coating. The overall planar dimensions are controlled to be 1cm × 1cm. Only the concentration of BTO-OH is changed in each layer, and the volume concentration of BTO-OH from the upper piezoelectric composite layer 4 to the lower piezoelectric composite layer 6 is continuously increasing, with a volume concentration range of 3.75% to 15%. The concentration difference between adjacent layers is controlled between 3% and 7%, so that the BTO-OH in the bottom piezoelectric composite layer 6 reaches the optimal concentration (this optimal concentration refers to the simultaneous satisfaction of the piezoelectric constant d). 33 The concentration range corresponding to the performance indicators of ≥40pC / N, dielectric loss tanδ≤0.05, and film density ≥95% was experimentally screened to be 13%-16%, with 14%-15.5% being preferred, and it also possesses the largest piezoelectric constant d. 33 The magnetostrictive layer 3 is composited on the bottom layer of the concentration gradient piezoelectric layer component 2 to achieve efficient magnetoelectric (ME) coupling. A silver electrode layer 1 is set on the surface of the concentration gradient piezoelectric layer component 2, and the generated electrical energy is collected and processed through the energy management module. This device does not have a mass block and support components. Only a temporary positioning structure is used during the fabrication process to ensure that the device realizes a pure ME energy conversion mechanism without the need for a vibration-assisted excitation module.
[0036] Another example is the concentration gradient piezoelectric layer assembly 2, with an overall concentration range of 3.75%-16%, ensuring that each layer has practical piezoelectric properties and good film formation. Concentration difference between adjacent layers: 3%-7%, a key control method to achieve multimodal response; The optimal concentration for the bottom layer is 11%-16%, preferably 14%-15.5%, while also satisfying d 33 ≥40 pC / N, tanδ≤0.05, film density≥95%; Example of a three-tiered progression: 3.75% (upper tier) / 7.5% (middle tier) / 15% (lower tier).
[0037] The working process is as follows: When the ambient magnetic field changes, it directly causes the magnetostrictive layer 3 to generate mechanical strain. This mechanical strain is directly transferred to each layer of the concentration gradient piezoelectric layer component 2 through the spin-coating interface without adhesive layer, realizing efficient conversion of magnetoelectric (ME) energy without the need for additional vibration-assisted excitation. Due to the differences in BTO-OH concentration and thickness in each layer of the concentration gradient piezoelectric layer component 2, their respective resonant frequencies are also different, thus causing the device to generate a multi-vibration peak response and realize multi-frequency magnetic field energy capture. The bottom layer adopts the optimal concentration (optimal concentration range: 11%-16% BTO-OH volume concentration; core preferred range: 14%-15.5%). 33A piezoelectric composite layer of BTO-OH (with peak value ≥42pC / N, optimal dielectric loss and film quality) (this optimal concentration is defined as simultaneously satisfying the piezoelectric constant d) 33 A BTO-OH volume concentration of ≥40pC / N, dielectric loss tanδ≤0.05, and film density ≥95% (specifically ranging from 11% to 16%, preferably 14% to 15.5%) can ensure the core efficiency of magnetoelectric conversion and further improve the energy output performance of the device.
[0038] Among them, when the optimal volume concentration of BTO-OH is <11%, d 33 <35pC / N, insufficient conversion efficiency; when the optimal BTO-OH volume concentration is >16%, tanδ>0.06, microcracks and agglomeration occur; therefore, the optimal concentration range is selected as 11%-16% BTO-OH volume concentration.
[0039] Example 2.
[0040] This embodiment is a multimodal broadband pure ME energy harvesting device without mass blocks, adhesive layers, or support components. Its specific component parameters and fabrication process are as follows.
[0041] (1) Component parameters; Concentration gradient piezoelectric layer component 2: This is an integrated structure without adhesive layers, prepared layer by layer by three P(VDF-TrFE) / BTO-OH piezoelectric composite layers via spin coating. The overall planar dimensions are 1cm × 1cm, with a total thickness of 100μm. Only the concentration of BTO-OH is varied in each layer, resulting in uniform layer thickness. The volume concentration of the ceramic filler BTO-OH is 3.75%, 7.5%, and 15% from top to bottom, with the bottom layer exhibiting the optimal BTO-OH concentration and its piezoelectric constant. d 33 =43pC / N, upper piezoelectric composite layer d 33 =21pC / N, middle piezoelectric composite layer d 33 =29pC / N.
[0042] Magnetostrictive layer 3: Made of Metglas 2605SA1 amorphous alloy, with a thickness of 32μm and a planar size of 1cm×1cm, it is tightly fixed to the bottom layer of concentration gradient piezoelectric layer component 2 through hot pressing composite method to ensure the stability of interlayer bonding.
[0043] Silver electrode layer 1: A highly conductive silver electrode with a thickness of 5 μm is prepared on the upper surface of the concentration gradient piezoelectric layer component 2 through a coating process. The electrode is independently led out through wires to effectively avoid signal interference and ensure stable collection of electrical energy.
[0044] like Figure 3 As shown, the fabrication method of the multi-mode broadband magnetoelectric energy harvesting structure provided in this embodiment of the invention includes: S1. Preparation of P(VDF-TrFE) / BTO-OH composite slurry; P(VDF-TrFE) / BTO-OH composite slurries with volume concentrations of 3.75%, 7.5%, and 15% were prepared respectively. Using N,N-dimethylformamide (DMF) as solvent, P(VDF-TrFE) powder (molecular weight 500,000) and BTO-OH particles (particle size 110 nm) were mixed in the corresponding proportions and ultrasonicated for 2 hours to disperse them evenly. Then, the slurries were degassed by ultrasonication at 200W power for 30 minutes to remove air bubbles and obtain a uniform and stable composite slurry.
[0045] S2. Complete the hot-pressing composite of magnetostrictive layer 3; During the fabrication process, a temporary support structure is used to fix the Metglas alloy sheet (this temporary support structure is only used for positioning during the fabrication process and does not constitute the structure of the device itself). Hot pressing composite is carried out according to the set process parameters (temperature 140℃, holding time 120min) to obtain the magnetoelectric composite substrate.
[0046] For example, the hot-pressing composite process parameters were optimized and determined as follows: when the temperature is below 135°C, the insufficient crystallinity of P(VDF-TrFE) leads to weak interfacial bonding; when the temperature is above 145°C, the brittleness of the Metglas alloy increases and it is prone to fracture; when the holding time is less than 110 min, the diffusion of interfacial molecular chains is insufficient and the strain transfer efficiency is less than 85%; when the holding time is more than 130 min, the piezoelectric layer is excessively oxidized, reducing the piezoelectric constant.
[0047] Using the preferred parameters of 140℃ and 120min of this invention, molecular-level interface contact is achieved compared to traditional epoxy resin adhesive layers (strain transfer efficiency is only about 70%). The measured strain transfer efficiency reaches 96%, and the device shows no delamination at the interface after aging in a humid heat environment of 85℃ / 85%RH for 1000h.
[0048] It can be seen that the key parameters in the hot pressing process are: hot pressing temperature < 120℃; P(VDF-TrFE) does not melt; and the bonding strength is < 5N / cm. Hot pressing temperature 130℃-145℃: moderate softening, peak bonding strength at 140℃ is 12N / cm; Hot pressing temperature > 150℃: thermal degradation, d 33 Decrease > 20%.
[0049] For example, time screening in hot-pressing composite: <60min: Insufficient bonding, strength <6N / cm; 90-150 min: The interface diffusion layer is 2-5 μm, with 120 min being optimal; >180 min: thermal oxidation, tanδ increases from 0.04 to 0.08.
[0050] For example, pressure screening in hot-pressing composite: <0.5MPa: Poor interface contact; 0.8-1.2MPa: tight fit, no air bubbles, 1.0MPa is optimal; >1.5MPa: The piezoelectric layer is excessively compressed, resulting in a decrease in performance.
[0051] S3. A concentration gradient piezoelectric layer assembly 2 was prepared by spin coating. The treated magnetoelectric composite substrate was fixed on the stage of a spin coater. First, a 15% concentration composite slurry was drop-coated onto the surface of a Metglas alloy sheet. The spin coater speed was set to 1200 rpm and the spin coater time was 30 s. Then, it was placed in an oven and heat-cured at 120°C for 30 min to form the lower piezoelectric composite layer 6. After it cooled to room temperature, the same method was used to spin coat a 7.5% concentration composite slurry (spin coater speed 1300 rpm, spin coater time 30 s) and a 3.75% concentration composite slurry (spin coater speed 1300 rpm, spin coater time 30 s). Each layer was heat-cured at 120°C for 30 min after spin coat. Layer by layer, a concentration gradient piezoelectric layer assembly 2 without an adhesive layer was formed, in which the middle piezoelectric composite layer 5 and the upper piezoelectric composite layer 4 were formed.
[0052] S4. Prepare silver electrode layer 1 and complete overall encapsulation; A silver electrode layer 1 is prepared on the upper surface of the concentration gradient piezoelectric layer component 2 by a coating process. After the lead wires are brought out, the edge of the device is encapsulated with a Kapton film to effectively prevent environmental moisture from corroding the device and ensure the long-term stable operation of the device, thus completing the fabrication of the entire device.
[0053] Example 3.
[0054] In another embodiment of the present invention, the concentration gradient piezoelectric layer component 2 adopts five layers with optimal concentration: five-layer gradient 3.75 / 5.5 / 7.5 / 11 / 15%, bandwidth 7.7kHz, and output 1.35V.
[0055] In another preferred embodiment of the present invention, the concentration gradient piezoelectric layer assembly 2 adopts a five-layer gradient structure, consisting of a first upper piezoelectric layer, a second upper piezoelectric layer, a middle piezoelectric layer, a second lower piezoelectric layer, and a bottom piezoelectric composite layer from top to bottom, replacing the original three-layer structure of upper piezoelectric composite layer 4, middle piezoelectric composite layer 5, and lower piezoelectric composite layer 6. The volume concentrations of the five BTO-OH layers from top to bottom are 3.75%, 5.5%, 7.5%, 11%, and 15%, respectively, with the bottom layer at 15% being the optimal piezoelectric concentration range. There is no adhesive layer between each layer, and the assembly is integrally spin-coated.
[0056] In the above embodiments, the descriptions of each embodiment have different focuses. For parts that are not described in detail or recorded in a certain embodiment, please refer to the relevant descriptions of other embodiments.
[0057] To further illustrate the effects of the embodiments of the present invention, the following experiments were conducted.
[0058] Experiment 1. To visually verify the technical advantages of this invention, the following comparative examples are provided and attached. Figure 4 , Figure 5 Comparison: Performance Testing and Results. To fully verify the technical effects of the present invention, in addition to Example 2 (a three-layer gradient structure with BTO-OH concentrations of 3.75%, 7.5%, and 15% respectively, with the bottom layer having the optimal concentration of 15%), three comparative examples were set up. All samples were tested for weak magnetic field energy harvesting performance under uniform test conditions to eliminate the influence of environmental and equipment differences on the test results.
[0059] Test conditions were standardized: the planar dimensions of all test samples were controlled to be 1 cm × 1 cm; the ambient temperature was 25℃ ± 2℃; the relative humidity was 45% ± 5%; and the same Helmholtz coil and lock-in amplifier test system was used. Excitation conditions were set as follows: ambient magnetic field strength 0.05 Oe; magnetic field frequency scan range 0–100kHz; and no external mechanical vibration excitation.
[0060] The structural parameters and test results of each sample are compared below. To visually verify the technical advantages of this invention, the following comparative examples and accompanying figures show a comparison of the vibration response of the device of this invention with that of a traditional single-concentration pure ME device. Figure 4 The vibration response diagram is for a traditional structure of the same thickness. Figure 5 This is a diagram showing the vibration response of the structure of the present invention. Comparative Example 1 (Traditional Single-Concentration Adhesive Structure): A single P(VDF-TrFE) / BTO-OH composite piezoelectric layer (approximately 100 μm thick) with a BTO-OH volume concentration of 10% was used, bonded to a Metglas alloy sheet (32 μm thick) via an epoxy resin adhesive layer, with a silver electrode placed on top. Test results show that, under the same dimensions (1 cm × 1 cm) and test conditions (0.05 Oe), this device exhibits only one resonance peak, with an effective energy harvesting bandwidth (defined as the frequency range where the output voltage ≥ 0.3 V) of 1.3 kHz and a peak output voltage of 0.42 V.
[0061] Comparative Example 2 (gradient structure with adhesive layer): The concentration gradient was the same as in Example 2 (top layer 3.75%, middle layer 7.5%, bottom layer 15%), but adjacent piezoelectric composite layers were bonded together with an epoxy resin adhesive layer of approximately 2–3 μm thickness. The remaining preparation process was consistent with Example 2. The test results showed a multi-peak response trend, but the effective bandwidth was only 4.7 kHz, and the peak output voltage was 0.68 V. Compared with Example 2, the introduction of the adhesive layer resulted in an interfacial strain transfer loss of approximately 43% (measured by voltage attenuation), severely limiting the bandwidth broadening effect and energy output capability.
[0062] Comparative Example 3 (gradient structure, but not optimal lower layer concentration): The concentration gradient was set to 3.75% for the upper layer, 7.5% for the middle layer, and 10% for the lower layer (the lower layer BTO-OH concentration was below the lower limit of the optimal concentration range of 11%). There was no adhesive layer between the layers, and the spin coating process was the same as in Example 2. The test results showed a multi-peak response, an effective bandwidth of 5.1 kHz, and a peak output voltage of 0.85 V, which is lower than the 1.2 V at the optimal concentration of this invention. This result confirms that using the optimal BTO-OH concentration in the bottom layer is one of the key factors in obtaining high-voltage output and wide-bandwidth response.
[0063] For example, the present invention is prepared as described in Example 2. The test results show three stable vibration peaks, corresponding to resonant frequencies of 4.05 kHz, 6.82 kHz and 8.71 kHz, with an effective energy harvesting frequency band of 2.7 kHz–9.0 kHz (bandwidth 6.3 kHz) and a peak output voltage of 1.20 V.
[0064] Broadening rate calculation: Based on the effective bandwidth of 1.3 kHz of Comparative Example 1 (traditional single-concentration adhesive structure), the effective bandwidth of Example 2 is 6.3 kHz. The broadening rate is calculated as: (6.3 kHz – 1.3 kHz) ÷ 1.3 kHz × 100% = 384.6%.
[0065] The comparative experiments above clearly demonstrate that the present invention, through the synergistic effect of the integrated fabrication of a concentration gradient piezoelectric layer, an adhesive-free layer, and the optimal concentration design of the bottom layer, significantly broadens the effective operating bandwidth and improves the output voltage under the same small size (1 cm × 1 cm) and weak magnetic field (0.05 Oe) conditions. In particular, the adhesive-free structure eliminates interfacial strain loss, and the optimal concentration of the bottom layer ensures the core efficiency of magnetoelectric coupling. Together, these factors result in a 384.6% increase in bandwidth compared to traditional single-concentration adhesive devices in Example 2, demonstrating outstanding substantive features and significant technological advancements.
[0066] Comparative Example 1 (Traditional Single Concentration): Single concentration 10%, epoxy resin bonding, bandwidth 1.3 kHz, output voltage 0.42V; Comparative Example 2 (with adhesive layer gradient): concentration gradient 3.75 / 7.5 / 15%, but with adhesive layer, bandwidth 4.7kHz, output 0.68V; Comparative Example 3 (Gradient + Non-optimal Lower Layer): Bottom layer 10% (<11%), bandwidth 5.1 kHz, output 0.85V; Example 2 (three layers + optimal concentration): bottom layer 15%, no adhesive layer, bandwidth 6.3 kHz, output 1.20V; In summary, the embodiments of the present invention achieve stable energy harvesting in the 2.7-9kHz frequency band, with a bandwidth that is 384.6% wider than that of Comparative Example 1 and an output voltage that is 185.7% higher. Among them, the test conditions are the same: all samples are tested under the conditions of 0.05Oe, 0-100kHz frequency sweep, and 25℃±2℃.
[0067] The concentration gradient piezoelectric layer component 2 in Example 3 uses five layers with optimal concentration: bandwidth 7.7kHz, output 1.35V; it has a much better effect than comparative examples 1-3.
[0068] For example, in Experiment 1 above, the bottom composite layer of the concentration gradient piezoelectric layer assembly 2 adopts the optimal concentration design of BTO-OH, which is in the range of 13%-16%, preferably 14%-15.5%, while satisfying d 33 ≥40pC / N, dielectric loss tanδ≤0.05, film density ≥95%, Among them, the upper layer (3.75%) has a low elastic modulus and dominates the low-frequency band (4 Hz); the middle layer (7.5%) has a medium elastic modulus and dominates the mid-frequency band (6.8kHz); the lower layer (15%) has a high elastic modulus and d 33 Maximum, dominating the high-frequency band (8.7kHz); three-layer segmented dominance and coordinated response, bandwidth extended to 6.3kHz.
[0069] For example, the pure ME energy conversion mechanism has no wear on vibrating parts, which extends the device's lifespan to more than 5000 hours in experiments.
[0070] Test standard: Refer to IEC 62830 series (piezoelectric energy harvesting devices); Test conditions: Environment: 25℃±2℃, relative humidity 45%±5% RH; Excitation: Continuously apply an alternating magnetic field of 0.05Oe, sweep frequency of 2.7-9kHz, 24h / cycle; Failure criteria: If the frequency covers the operating frequency band and the output voltage drops below 80% of the initial value, it is considered a failure; or if mechanical damage / delamination occurs. Test results: After 5000 hours of continuous operation, the output voltage remained above 85% of the initial value; there were no mechanical failures such as interlayer peeling or microcrack propagation.
[0071] The above description is only a preferred embodiment of the present invention, but the scope of protection of the present invention is not limited thereto. Any modifications, equivalent substitutions and improvements made by those skilled in the art within the scope of the technology disclosed in the present invention and within the spirit and principles of the present invention should be covered within the scope of protection of the present invention.
Claims
1. A multi-mode broadband magnetoelectric energy harvesting structure, characterized in that, The structure includes a concentration gradient piezoelectric layer assembly (2), a magnetostrictive layer (3), and a silver electrode layer (1). The concentration gradient piezoelectric layer assembly (2) is integrally formed by spin coating of an upper piezoelectric composite layer (4), a middle piezoelectric composite layer (5), and a lower piezoelectric composite layer (6), with no adhesive layer between the layers. The magnetostrictive layer (3) is tightly bonded to the lower piezoelectric composite layer (6), and the silver electrode layer (1) covers the upper piezoelectric composite layer (4), forming a flat, compact magnetoelectric energy harvesting structure.
2. The multi-mode broadband magnetoelectric energy harvesting structure according to claim 1, characterized in that, The upper piezoelectric composite layer (4), the middle piezoelectric composite layer (5), and the lower piezoelectric composite layer (6) all adopt the P(VDF-TrFE) / BTO-OH composite system and are prepared layer by layer by spin coating. The overall planar size of the concentration gradient piezoelectric layer assembly (2) is 1cm×1cm.
3. The multi-mode broadband magnetoelectric energy harvesting structure according to claim 2, characterized in that, The BTO-OH volume concentration inside the upper piezoelectric composite layer (4), the middle piezoelectric composite layer (5), and the lower piezoelectric composite layer (6) is distributed in a continuously increasing gradient along the thickness direction. The BTO-OH volume concentration ranges from 3.75% to 16%, and the concentration difference between adjacent layers is controlled between 3% and 7%.
4. The multimodal broadband magnetoelectric energy harvesting structure according to claim 3, characterized in that, The optimal volume concentration of BTO-OH in the lower piezoelectric composite layer (6) is 14% to 15.5%.
5. The multi-mode broadband magnetoelectric energy harvesting structure according to claim 1, characterized in that, The magnetostrictive layer (3) is made of amorphous alloy material and has a planar size of 1cm×1cm; the silver electrode layer (1) is made of highly conductive silver electrode and is prepared on the upper surface of the upper piezoelectric composite layer (4) by coating process.
6. A method for fabricating a multi-mode broadband magnetoelectric energy harvesting structure, characterized in that, This preparation method is used to prepare the multimodal broadband magnetoelectric energy harvesting structure according to any one of claims 1-5, and the preparation method includes: S1. Preparation of P(VDF-TrFE) / BTO-OH composite slurry; S2, complete the hot-pressing composite of the magnetostrictive layer (3); S3. A concentration gradient piezoelectric layer assembly was prepared by spin coating (2). S4. Prepare the silver electrode layer (1) and complete the overall encapsulation.
7. The method for fabricating the multimode broadband magnetoelectric energy harvesting structure according to claim 6, characterized in that, In step S1, the preparation of P(VDF-TrFE) / BTO-OH composite slurry includes: P(VDF-TrFE) / BTO-OH composite slurries with volume concentrations of 3.75%, 7.5%, and 15% were prepared respectively. Using N,N-dimethylformamide (DMF) as a solvent, P(VDF-TrFE) powder and BTO-OH particles were mixed in proportion. The particles were ultrasonically dispersed for 2 hours to ensure uniform dispersion, and then ultrasonically degassed for 30 minutes at 200W power to remove air bubbles, resulting in a uniform and stable composite slurry.
8. The method for fabricating the multimode broadband magnetoelectric energy harvesting structure according to claim 6, characterized in that, In step S2, the hot-pressing composite of the magnetostrictive layer (3) includes: A temporary support structure was used to fix the Metglas amorphous alloy sheet, and hot-pressing composite was carried out under the process conditions of 140℃, 120 min holding time, and 0.8–1.2 MPa pressure to obtain a stable magnetoelectric composite substrate.
9. The method for fabricating the multimode broadband magnetoelectric energy harvesting structure according to claim 6, characterized in that, In step S3, the concentration gradient piezoelectric layer assembly (2) is prepared by spin coating, including: The magnetoelectric composite substrate was fixed on the stage of the spin coater. First, a 15% concentration composite slurry was dropped onto the surface of the Metglas alloy sheet. The spin coating speed was 1200 rpm and the spin coating time was 30 s. Then, it was heat-cured at 120℃ for 30 min to form the lower piezoelectric composite layer (6). After cooling to room temperature, the same process was used to spin coat 7.5% and 3.75% concentration composite slurries. Each spin coating was heat-cured at 120℃ for 30 min. Layer by layer, a gradient piezoelectric overall structure without adhesive layer was formed, and the middle piezoelectric composite layer (5) and the upper piezoelectric composite layer (4) were formed in sequence.
10. The method for fabricating the multimode broadband magnetoelectric energy harvesting structure according to claim 9, characterized in that, The concentration gradient piezoelectric layer assembly (2) adopts a five-level gradient concentration layer design, with the five gradient volume concentrations being 3.75%, 5.5%, 7.5%, 11%, and 15% respectively, forming a continuously gradually changing concentration gradient piezoelectric structure.
